Acoustic and Elastic Waves: Recent Trends in Science and Engineering - Nathalie Godin (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
The present Special Issue intends to explore new directions in the field of acoustics and ultrasonics. The interest includes, but is not limited to, the use of acoustic technology for condition monitoring of materials and structures. Topics of interest (among others): • Acoustic emission in materials and structures (without material limitation) • Innovative cases of ultrasonic inspection • Wave dispersion and waveguides • Monitoring of innovative materials • Seismic waves • Vibrations, damping and noise control • Combination of mechanical wave techniques with other types for structural health monitoring purposes. Experimental and numerical studies are welcome.